PENGARUH PENGGUNAAN MEDIA MODEL TERHADAP HASIL BELAJAR ILMU BANGUNAN GEDUNG KELAS X TEKNIK BANGUNAN SMKN 1 PADANG - 83-91 . Rani Yulia (CIVED, 2013)
This study aims to determine the different of media use models in teaching Science Building on the results of class X students of Engineering Building SMKN 1 Padang. This study is a quasi-experimental Pre-test Post- test Non-Equivalent Control Group Design. Cluster sampling using random sampling. Data collection instruments such as achievement test. The results of this study concluded that there was a significant effect of the use of media in teaching models Sciences Building on student learning outcomes. The use of media in learning models help students remember, understand, analyze, evaluate and create so that the learning objectives are achieved and improved student learning outcomes. Key words :        media model, hasil belajar